The Influence of Price, Location and Service Quality on Purchasing Decisions with Purchase Interest as an Intervening Variable at Transmart Padang - Bismark, Irma Auliyah; Yulasmi, Yulasmi; Lusiana, Lusiana (UPI YPTK Journal of Business and Economics, 2023)
This study aims to determine and analyze the influence of price, location, and service quality on purchasing decision with purchasing interest as intervening variables at Transmart Padang. There are some variables need to be ensured on this study. They are the influence of price, location and service quality on interest at Transmart Padang. Another one is the influence of purchasing interest on purchasing decisions at Transmart Padang City. Besides, there is also the influence of price, location and service quality on purchasing decisions at Transmart Padang through purchasing interest as an intervening variable. This research was conducted using a descriptive and causal research design and samples were taken using a non-probability-silling sample design using accidental sampling technique. In this study, the number of samples was 100 people. While the research instrument was a questionnaire using a Likert scale. Structural Equation Modeling (SEM) analysis were used as data analysis techniques in this study. The results showed that location had no significant effect on consumer purchasing interest at Transmart Padang, while price and service quality had a significant effect on consumer buying interest at Transmart Padang. Service quality had no significant effect on purchasing decisions at Padang City Transmart, while price, location and purchasing intention had a significant effect on purchasing decisions at Transmart Padang. Location had no significant effect on purchasing decisions at Transmart Padang through purchasing intention, while price and service quality had a significant effect on purchasing decisions at Transmart Padang through purchase intention.